A recurrent mutation in TSHB gene underlying central congenital hypoyhyroidism undetectable in neonatal screening - Borges, Maria de Fátima (2019)
Objective: To describe the case of a patient with central congenital hypothyroidism (CCH) due to a recurrent mutation in the TSHB gene, as well as to conduct a genetic study of his family. Case description: It is presented a case report of a 5-monthold boy with a delayed diagnosis of isolated CCH in whom the molecular analysis was performed 12 years later and detected a recurrent mutation (c.373delT) in TSHB gene. The parents and sister were carriers of the mutant allele. Comments: The c.373delT mutation has previously been reported in patients from Brazil, Germany, Belgium, United States, Switzerland, Argentina, France, Portugal, United Kingdom and Ireland. In summary, our case and other ones reported in the literature support the theory that this mutation may be a common cause of isolated TSH deficiency. Isolated TSH deficiency is not detected by routine TSH-based neonatal screening, representing a clinical challenge. Therefore, when possible, molecular genetic study is indicated. Identification of affected and carriers allows the diagnosis, treatment and adequate genetic counseling.